Development of digital comic media for improving student learning outcomes in collective lifestyle material - Novi Astika Rambe; Daulat Saragi; Waminton Rajagukguk (Himpunan Pengembang Kurikulum Indonesia, 2025)
Digital comics are now rapidly evolving as an innovative learning medium that captures students' interest through visual and interactive presentations, making comprehension easier and enhancing their engagement in the learning process. This study aims to develop a digital comic medium that is valid, practical, and effective in supporting learning and improving the learning outcomes of fourth-grade students at SDN 165733 Tebing Tinggi. The research method employed is development research, based on the ADDIE model, which encompasses the stages of analysis, design, development, implementation, and evaluation. During the development process, the digital comic was validated by experts in content, media, and language and tested on fourth-grade students (Class IV-2) using pre- and post-test questions to measure learning improvement. The study results indicate that the digital comic medium is highly feasible, as validated by experts. Additionally, it has proven effective in enhancing students' learning outcomes, as evidenced by a significant increase in pre-test and post-test scores. The digital comic, developed using Canva, is considered highly feasible, practical, and effective as a learning tool, particularly in Pancasila Education, due to its engaging and interactive presentation. Abstrak Komik digital kini berkembang pesat sebagai media pembelajaran inovatif yang menarik perhatian peserta didik melalui tampilan visual dan interaktif, sehingga mempermudah pemahaman serta meningkatkan keterlibatan mereka dalam proses belajar. Penelitian ini bertujuan untuk mengembangkan media komik digital yang valid, praktis, dan efektif guna mendukung pembelajaran serta meningkatkan hasil belajar peserta didik kelas IV di SDN 165733 Tebing Tinggi. Metode yang diterapkan adalah penelitian pengembangan dengan model ADDIE, yang mencakup tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Dalam prosesnya, media komik ini divalidasi oleh para ahli di bidang materi, media, dan bahasa, serta diuji coba pada peserta didik kelas IV-2 menggunakan soal pretest dan posttest untuk mengukur peningkatan hasil belajar. Hasil penelitian menunjukkan bahwa media komik digital ini dinilai sangat layak berdasarkan validasi para ahli. Selain itu, media ini terbukti efektif dalam meningkatkan hasil belajar peserta didik, sebagaimana terlihat dari peningkatan signifikan antara nilai pretest dan posttest. Komik digital yang dikembangkan melalui Canva ini dinilai sangat layak, praktis, dan efektif sebagai alat bantu pembelajaran, terutama dalam mata pelajaran Pendidikan Pancasila, berkat penyajiannya yang menarik dan interaktif. Kata Kunci: gotong royong; Hasil belajar; Komik digital; Media pembelajaran